HUBUNGAN KECERDASAN EMOSI DENGAN TEKANAN PELAJAR MENGHADAPI PEMBELAJARAN SECARA ATAS TALIAN SEMASA PANDEMIK WABAK COVID-19 - Mamat, Suzyliana; Alias, Atini; Abdullah, Norhasima; Wan Othman, Wan Norhayati; Yahya, Siti Aishah (Jurnal 'Ulwan, 2023)
In 2020, the whole world was shaken by epidemic of Covid-19. This spread of epidemic cause all face-to-face communcation to be disrupted. People started to communicate online including learning activities. Ttherefore, this study aims to examine the relationship between emotional intelligence and the stress of students facing online learning during the Covid-19 pandemic. The study sample consisted of 110 students from Institutes of Higher Education (IPT) around Alor Gajah, Melaka by using a simple sampling technique where the whole the population involved has the same opportunity as a respondent. Data collection is using computer software applications namely Statistical Package for Social Sciences (SPSS) to analyze statistical data. The results of data analysis are descriptive and inferential. The questionnaire is divided into three parts, namely part A Demographic Factors, part B Emotional Intelligence Questionnaire and part C Stress Questionnaire. The results of the study show that there is a significant relationship between emotional intelligence and stress among students, the value of which is r= -.434, k